Arabidopsis SnRK1 negatively regulates phenylpropanoid metabolism via Kelch domain-containing F-box proteins - Wang, Bin; Zhao, Xianhai; Zhao, Yunjun; Shanklin, John; Zhao, Qiao; Liu, Chang-Jun (The New phytologist, 2021)
• Phenylpropanoid metabolism represents a substantial metabolic sink for photosynthetically fixed carbon. The evolutionarily conserved Sucrose Non-Fermenting Related Kinase 1 (SnRK1) is a major metabolic sensor that reprograms metabolism upon carbon deprivation. However, it is not clear if and how the SnRK1-mediated sugar signaling pathway controls phenylpropanoid metabolism. • Here, we show that Arabidopsis SnRK1 negatively regulates phenylpropanoid biosynthesis via a group of Kelch domain-containing F-box (KFB) proteins that are responsible for the ubiquitination and degradation of phenylalanine ammonia lyase (PAL). • Downregulation of AtSnRK1 significantly promoted the accumulation of soluble phenolics and lignin polymers and drastically increased PAL cellular accumulation but only slightly altered its transcription level. Co-expression of SnRK1α with PAL in Nicotiana benthamiana leaves resulted in the severe attenuation of the latter’s protein level, but protein interaction assays suggested PAL is not a direct substrate of SnRK1. Furthermore, up or downregulation of AtSnRK1 positively affected KFBPALs gene expression, and energy starvation upregulated KFBPAL expression, which partially depends on AtSnRK1. • Collectively, our study reveals that SnRK1 negatively regulates phenylpropanoid biosynthesis, and KFBPALs act as regulatory components of the SnRK1 signaling network, transcriptionally regulated by SnRK1 and subsequently mediate proteasomal degradation of PAL in response to the cellular carbon availability.